2008
DOI: 10.2478/s11756-008-0043-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of a new composite biomaterial fluor-hydroxyapatite on fibroblast cell line NIH-3T3 by direct test

Abstract: The number of biomaterials used in biomedical applications has rapidly increased in the past two decades. Fluorapatite (FA) is one of the inorganic constituents of bone or teeth used for hard tissue repairs and replacements. Fluor-hydroxyapatite (FHA) is a new synthetically prepared composite that in its structure contains the same molecular concentration of OH − groups and F − ions. The aim of this experimental investigation was to use the embryonal mouse fibroblast cell line NIH-3T3 for comparative study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…It is interesting the range of the concentration because the material can be cytotoxic at some concentration and in other it cannot, besides, it is important to create a similar body fluid on the biomaterial contact. Therefore, these materials did not significantly affect the cell viability, being non-cytotoxic, corroborating with recent literature results [21,22].…”
Section: Xtt Analysissupporting
confidence: 92%
“…It is interesting the range of the concentration because the material can be cytotoxic at some concentration and in other it cannot, besides, it is important to create a similar body fluid on the biomaterial contact. Therefore, these materials did not significantly affect the cell viability, being non-cytotoxic, corroborating with recent literature results [21,22].…”
Section: Xtt Analysissupporting
confidence: 92%
“…Theiszova and co-workers have shown that the 3T3 fibroblast is appropriate for measuring the cytotoxicity of biomaterials. 43 Moreover, because it is a commonly utilized cell line, it provides a good system for comparison of nanomaterial safety as developed by different research groups. As key cellular components of the innate immune system, macrophages readily phagocytose foreign materials, including most nanoparticles, 44,45 and thus the in vitro toxicity response of RAW 264.7 macrophages is thought to provide preliminary insight on potential immune recognition of nanomaterials.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As the toxicity response to nanomaterials has previously proved to be cell-type dependent, , the present study compared the cytotoxicity of hyperbranched polymers in two different cell lines, 3T3 fibroblasts and RAW264.7 macrophages. Theiszova and co-workers have shown that the 3T3 fibroblast is appropriate for measuring the cytotoxicity of biomaterials . Moreover, because it is a commonly utilized cell line, it provides a good system for comparison of nanomaterial safety as developed by different research groups.…”
Section: Resultsmentioning
confidence: 99%
“…Similar G0/G1 arrest and inhibition in the cell proliferation were found in FA treated NIH-3T3 cells, revealing the harmful genotoxic effect of uoridated biomaterial eluates. 143,144 Heil et al 17 reported a thorough study on the mutagenesis/ carcinogenesis of dental material extract, using three fast and reliable test systems, namely the bacterial umuC-test, the eukaryotic DNA synthesis inhibition test and an in vivo alkaline lter elution technique. The bacterial umuC test, using the Salmonella typhimurium strain, is as sensitive as an Ames test, with a umuC operon capable of being induced by genotoxic agents.…”
Section: Biological Response To Wear Particulatesmentioning
confidence: 99%